Intergenerational education mobility among the children of Canadian immigrants - Abdurrahman Aydemir; Wen-Hao Chen; Miles Corak (Institute for the Study of Labor (IZA), 2008)
We analyze the intergenerational education mobility of Canadian men and women born to immigrants. A detailed portrait of Canadians is offered, as are estimates of the degree of generational mobility among the children of immigrants. Persistence in the years of schooling across the generations is rather weak between immigrants and their Canadian born children, and a third as strong as for the general population. Parental earnings is not correlated with years of schooling for second generation children, and if anything negatively correlated. Finally we find that the intergenerational transmission of education has not changed across the birth cohorts of the post-war period.
urn:nbn:de:101:1-20081126120
Keywords: F22; 330; Immigrants; education; intergenerational mobility; Internationale Wanderung; Migranten; Kinder; Bildungsverhalten; Intergenerational Mobility; Kanada